Changes in hot spring temperature and hydrogeology of the Alpine Fault hanging wall, New Zealand, induced by distal South Island earthquakes. Issue 1 (19th September 2014) - Cox, S. C.; Menzies, C. D.; Sutherland, R.; Denys, P. H.; Chamberlain, C.; Teagle, D. A. H.
Abstract: Thermal springs in the Southern Alps, New Zealand, originate through penetration of fluids into a thermal anomaly generated by rapid uplift and exhumation on the Alpine Fault. Copland hot spring (43.629S, 169.946E) is one of the most vigorously flowing, hottest of the springs, discharging strongly effervescent CO2 ‐rich 56–58°C water at 6 ± 1 l sec −1 . Shaking from the Mw7.8 Dusky Sound (Fiordland) 2009 and Mw7.1 Darfield (Canterbury) 2010 earthquakes, 350 and 180 km from the spring, respectively, resulted in a characteristic approximately 1°C delayed cooling over 5 days. A decrease in conductivity and increase in pH were measured following the Mw7.1 Darfield earthquake. Earthquake‐induced decreases in Cl, Li, B, Na, K, Sr and Ba concentrations and an increase in SO4 concentration reflect higher proportions of shallow‐circulating meteoric fluid mixing in the subsurface. Shaking at amplitudes of approximately 0.5% g Peak Ground Acceleration (PGA) and/or 0.05–0.10 MPa dynamic stress influences Copland hot spring temperature, which did not respond during the Mw6.3 Christchurch 2011 aftershock or other minor earthquakes. Such thresholds should be exceeded every 1–10 years in the central Southern Alps. The characteristic cooling response at low shaking intensities (MM III–IV) and seismic energy densities (approximately 10 −1 J m −3 ) from intermediate‐field distances was independent of variations in spectral frequency, without the need for post‐seismic recovery. Observed temperature and fluid chemistry responses are inferred to reflect subtle changes in the fracture permeability of schist mountains adjacent to the spring. Permanent 10 −7 –10 −6 strains recorded by cGPS reflect opening or generation of fractures, allowing greater quantities of relatively cool near‐surface groundwater to mix with upwelling hot water. Active deformation, tectonic and topographic stress in the Alpine Fault hanging wall, where orographic rainfall, uplift and erosion are extreme, make the Southern Alps hydrothermal system particularly susceptible to earthquake‐induced transient permeability. Abstract : In response to large distant earthquakes Copland hot spring cooled approximately 1°C and changed fluid chemistry. Relatively low intensity shaking induced small permanent strains across the Southern Alps – opening fractures which enhanced mixing of relatively cool near‐surface groundwater with upwelling hot water. Active deformation, tectonic and topographic stress in the Alpine Fault hanging wall makes the Southern Alps hydrothermal system particularly susceptible to earthquake‐induced transience.